Differences in cancer incidence by age at diagnosis between Aboriginal and non-Aboriginal people for cancer types included in Australian national screening programs. (June 2019) - Tervonen, Hanna E.; Morrell, Stephen; Roder, David; You, Hui; Currow, David C.
Highlights: Higher proportions of breast/ bowel cancers were diagnosed before the screening target age range in Aboriginal people. Age-specific breast/ bowel cancer incidence rates were higher in older Aboriginal vs. non-Aboriginal people. All age-specific cervical cancer incidence rates were higher in Aboriginal vs. non-Aboriginal people. Abstract: Background: This study examined age distributions and age-specific incidence of screened cancers by Aboriginal status in New South Wales (NSW) to consider the appropriateness of screening target age ranges. Methods: The NSW Cancer Registry identified invasive (female) breast, cervical and bowel cancers in people diagnosed in 2001–2014. Results: Aboriginal people were younger at diagnosis with higher proportions of breast and bowel cancers diagnosed before the screening target age range (<50 years) compared with non-Aboriginal people (30.6% vs. 22.8%, and 17.3% vs. 7.3%, respectively). Age-specific incidence rate ratios (IRRs) were lower/similar for breast and bowel cancers in younger and higher in older Aboriginal than non-Aboriginal people. All age-specific cervical cancer IRRs were higher for Aboriginal compared with non-Aboriginal people. Conclusion: Although higher proportions of breast and colorectal cancers were diagnosed before screening commencement age in Aboriginal people, this does not necessarily indicate a need for earlier screening commencement. Other aspects needing consideration include benefits, harms and cost-effectiveness.